Sizing of Fast Frequency Response Reserves for improving frequency security in low-inertia power systems - Panagi, Savvas; Aristidou, Petros (My University, 2025)
The increasing penetration of Renewable Energy Sources (RES) in electricity grids has led to the gradual decommissioning of conventional generators and, thus, to a decrease in the available inertia and other frequency support reserves. Consequently, the frequency security of power systems, in particular islanded low-inertia ones, is compromised, leading to faster and more extreme frequency deviations following disturbances. There is an urgent need to incorporate faster frequency reserves that can stabilize the system and enhance its resilience and reliability. This paper first investigates the impact of various frequency support mechanisms on the system frequency security in low-inertia grids. Then, we propose a novel, data-driven, gradient-descent-based method, that combines Dynamic Security Assessment (DSA) with linear predictions to optimize Fast Frequency Response (FFR) sizing for low-inertia grids. The performance of the proposed approach is evaluated using the dynamic model of Cyprus across 500 selected historical operating scenarios. The results demonstrate fast convergence, achieving the target frequency Nadir with minimal computational effort.
Keywords: Fast Frequency Response (FFR); BESS sizing; frequency security; low-inertia grids